Coincidence Best Proximity Point Results in Branciari Metric Spaces with Applications. (14th December 2020) - Saleem, Naeem; De la Sen, Manuel; Farooq, Sadia
Abstract : This paper is aimed at studying the uniqueness of coincidence best proximity point for ϑ, α +, g -proximal contractions in complete Branciari metric space. Throughout this article, discontinuity of the Branciari metric space is used and we obtained the desired results without assuming it as a continuous. Some examples are provided to validate the results proved herein. As an application, we derive the best proximity point results in the setup of complete Branciari metric space endowed with graph. Further, our results extend and generalize the existing ones in literature.